2023
DOI: 10.3389/fphar.2023.1196287
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as an emerging therapeutic target in liver diseases

Yuzhen Lu,
Junjie Hu,
Liang Chen
et al.

Abstract: Ferroptosis is an iron-dependently nonapoptotic cell death characterized by excessive accumulation of lipid peroxides and cellular iron metabolism disturbances. Impaired iron homeostasis and dysregulation of metabolic pathways are contributors to ferroptosis. As a major metabolic hub, the liver synthesizes and transports plasma proteins and endogenous fatty acids. Also, it acts as the primary location of iron storage for hepcidin generation and secretion. To date, although the intricate correlation between fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…The study identified different GPX4 isoforms with opposing effects on ferroptosis in hepatocytes, indicating the complex regulation of ferroptosis [53]. Both ferroptosis inducers and inhibitors provide promising therapeutic opportunities along the spectrum of MASLD to hepatocellular carcinoma [54]. Nevertheless, the underlying mechanisms in ferroptosis and their iron-related effects on MASLD progression still have to be studied in detail [55].…”
Section: Oxidative Stress and Metabolic-dysfunction-associated Steato...mentioning
confidence: 99%
“…The study identified different GPX4 isoforms with opposing effects on ferroptosis in hepatocytes, indicating the complex regulation of ferroptosis [53]. Both ferroptosis inducers and inhibitors provide promising therapeutic opportunities along the spectrum of MASLD to hepatocellular carcinoma [54]. Nevertheless, the underlying mechanisms in ferroptosis and their iron-related effects on MASLD progression still have to be studied in detail [55].…”
Section: Oxidative Stress and Metabolic-dysfunction-associated Steato...mentioning
confidence: 99%